A structural understanding of influenza virus genome replication - Zhu, Z; Fodor, E; Keown, J (Cell Press, 2022)
Influenza virus contains a single-stranded negative-sense RNA genome. Replication of the genome is carried out by the viral RNA-dependent RNA polymerase in the context of the viral ribonucleoprotein (RNP) complex, through a positive-sense complementary RNA intermediate. Genome replication is tightly controlled through interactions with accessory viral and host factors. Propelled by developments in recombinant protein expression, and technical improvements in X-ray crystallography and cryo-electron microscopy, snapshots of the replication process have been captured. Here, we review how recent structural data shed light on the molecular mechanisms of influenza virus genome replication, in particular, encapsidation of nascent RNA, de novo RNP assembly, and regulation of replication initiation through interactions with host and viral cues.